The Role of Executive in Academic Management of Early Childhood Education in Primary Educational Service Area Office Section 1 in Nonthaburi Province - แย้มแฟง เปรมจิต (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
Research results the purposes of this research was to compare the roles of administrators in the management of early childhood education in schools under the Office of Nonthaburi Primary Education Area 1. The samples consisted of 198 people selected by simple random sampling method and categorized by gender, status, work experiences and educational background. The samples of this study were, administrators, academic teacher and teachers in schools under the Office of Nonthaburi Primary Education Area 1. The data were collected by 5 range-rating-scale-questionnaire with index of consistency: IOC 0.89 descriptive statistics were the method used in this study by showing general information with percentage, mean, standard deviation, t-test, One-way ANOVA, and LSD. The research found that the roles of administrators in early childhood academic administration in educational institutions under the Office of Nonthaburi Primary Education Area 1 who had different gender, status, work experiences and educational background had no different opinion in total of the management of early childhood education in schools, curriculum development, teaching and learning, media, innovation and technology support for teaching and learning, educational evaluation, internal supervision, classroom research.